When rhinosinusitis is not just rhinosinusitis: Clinical characteristics and phenotypes of patients with type 2 chronic rhinosinusitis with nasal polyps: CRwNP clinical characteristics and phenotype - La Mantia, Ignazio; Ciprandi, Giorgio; Varricchio, Attilio; Ragusa, Martina; Cipolla, Federica; Andaloro, Claudio (Acta Biomedica Atenei Parmensis, 2022)
Background and aim: Chronic rhinosinusitis (CRS) is a chronic and recurrent disease that negatively affects patients’ quality of life. CRS has two main phenotypes: CRS with nasal polyps (CRSwNP) and CRS without polyps (CRSsNP). Minimal research has been conducted to study the variability in patients’ characteristics. Therefore, we conducted this study to examine these differences. Methods: A retrospective cohort study included patients with both CRSwNP and CRSsNP. Outcomes included symptom severity, radiographic severity, and number of sinus surgeries. Symptom severity was assessed using the Sino-nasal Outcome Test and the Lund-Mackay CT score was used to determine radiographic severity. Further subgroup analysis was done based on the presence or absence of comorbid asthma. Results: A total of 110 and 106 patients were included in the CRSwNP and CRSsNP groups, respectively. The mean age in the CRSwNP and CRSsNP groups was 50.2 and 48.7, and the proportion of female patients was 40.9% and 58.5%, respectively. No significant difference in symptom severity was noted between CRSwNP and CRSsNP group (68.1±18.6 vs. 73.2±21.27; P=0.097), while the Lund-Mackay score was significantly lower in the CRSsNP group (7.4±2.3 vs. 11.9±3.6; P=0.016). Also, the number of surgeries was significantly lower in the CRSsNP group as compared to the CRSwNP group (P=0.023). Subgroup analysis revealed statistically significant differences between those with and without asthma in patients with CRSwNP in terms of Lund-Mackay scores and number of surgeries (P=0.038 and 0.043), respectively. However, no significant differences were noted in the CRSsNP group (P>0.05). Conclusions: There is a clear variability in the characteristics of patients with CRSsNP and CRSwNP. A similar difference was noted in the CRSwNP group when patients were stratified based on the presence of absence of asthma. This warrants further investigation of potential correlation with the prognosis and optimum treatment strategies of this patient population